INITIAL EXPERIENCE WITH KIDNEY TRANSPLANTATION FROM BRAIN-DEAD DONORS AT THONG NHAT HOSPITAL: A CASE SERIES OF FOUR CLINICAL CASES - Văn Quảng, Lý; Hữu Toàn, Võ; Bá Quốc, Nguyễn; Trọng Lãm, Nguyễn; Tiến Luật, Mai (Journal of Health and Aging, 2025)
In Vietnam, kidney transplantation has been performed since 1992. However, the number of transplants remains limited, mainly due to reliance on living donors. Expanding the donor pool with brain-dead donors is considered a humane and sustainable solution to address the current organ shortage, particularly in kidney transplantation. Since May 2022, Thong Nhat Hospital has launched a kidney transplant program with technical support from Cho Ray Hospital. As of March 2025, we have successfully performed 21 kidney transplants, including 4 cases using kidneys from 2 brain-dead donors. This is a descriptive clinical study of the first 4 kidney transplants using organs from 2 brain-dead donors, performed on November 24, 2024, and March 19, 2025. There were two brain-dead donors: the first was a male, 18 years old, who died from traumatic brain injury, with 174 hours between injury and brain death diagnosis; the second was a male, 44 years old, who suffered a fatal occupational accident, with 45 hours from accident to brain death confirmation. Renal function in both donors was assessed before organ retrieval. Four recipients with end-stage chronic kidney disease undergoing regular hemodialysis were selected, including 3 males and 1 female, with a mean age of 33.25 years. Two kidneys were transplanted into the right iliac fossa and two into the left. All patients produced urine immediately on the operating table. The average operative time was 270 minutes, with arterial and venous anastomosis times averaging 15.5 and 12.5 minutes, respectively. Vascular anastomoses were performed in an end-to-side fashion. Ureteroneocystostomy was performed using the Lich-Grégoir technique with JJ stent placement. Renal function recovered rapidly within one week in the first two patients, while the other two experienced delayed recovery. One female patient underwent reoperation on postoperative day 13 due to perinephric fluid and hematoma; her condition stabilized after drainage and she was discharged one week later. Initial results suggest that kidney transplantation from brain-dead donors is feasible at Thong Nhat Hospital. Although technical support from Cho Ray Hospital is still necessary, the surgical team at Thong Nhat has gradually gained control over key steps of the transplant procedure. Compared to living-donor transplants, kidneys from brain-dead donors tend to have slower functional recovery. However, from a surgical standpoint, vascular anastomoses are more straightforward due to the presence of vascular patches, which facilitate safer and easier anastomosis. Kidney transplantation from brain-dead donors is a humane, safe, and effective solution that significantly improves the quality of life for end-stage renal disease patients and serves as a strategic direction for organ transplantation development at Thong Nhat Hospital.
Keywords: Kidney transplantation; brain-dead donor; vascular patch; Thong Nhat Hospital; initial experience